Germany : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Germany's growth momentum has remained solid, underpinned by robust domestic demand. In 2016, strong employment growth continued to support private consumption, while public consumption and investment in construction accelerated further. Following a soft patch for most of the year, exports and investments in equipment have rebounded in the most recent quarters. Real GDP is expected to grow by 1.8 percent in 2017 and 1.6 percent in 2018, increasing the already positive output gap and pushing up core inflation. Over the medium term, population aging and slow progress on structural reforms is expected to weigh on growth.